PROBLEMATIKA GURU HONORER TERKAIT KEBIJAKAN REKRUTMEN GURU PPPK - Zunita, Irma; Fadriati, Fadriati (Jurnal Manajemen Pendidikan, 2022)
Starting in 2021, the government will stop the recruitment of prospective civil servants in teacher formations, and will be replaced by the government employee with a work agreement (PPPK). This study aims to analyze the policy of terminating the recruitment of PNS teachers. This type of research is policy research. Research is carried out through a series of activities, beginning with research preparation, research implementation, and ending with the preparation of action-oriented recommendations. Based on the study of the government's reasons regarding the recruitment of CPNS to become PPPK, it is based on the contents of law number 5 of 2014 concerning ASN that the state civil apparatus consists of civil servants (PNS) and government employees in work agreements (PPPK), both of whom have positions, duties and responsibilities. and the same responsibility in providing good public services to the community. With this dismissal, teachers who are already civil servants will be retained until retirement.